STRUKTUR ORGANISASI TIM PENGELOLA LMS UNTUK EFESIENSI OPERASIONAL - Nurhabibah; Ahmad Subagyo; Zulfitria (STKIP Subang, 2025)
Learning Management System (LMS) in education has experienced a significant increase in recent years. This article aims to (1) Describe the operational impact of the absence of a clear LMS team organisation structure. (2) To formulate the main components or functions that need to be present in the LMS management team structure. This article results in (1) LMS management is often assigned to only one or two people without a clear division of tasks. This causes delays in handling technical problems, lack of user training, and no thorough monitoring of the effectiveness of LMS use. (2) To achieve operational efficiency, the LMS management team structure needs to be organised and functional. Each team member should have a clear and complementary role.